Development and validation of selective and sensitive LC-MS/MS Methods for determination of para-aminosalicyclic acid and cycloserine/terizidone applicable to clinical studies for the treatment of tuberculosis - Smit, Michiel Johannes (Division of Clinical Pharmacology, 2019)
A method was validated for the quantification of para-aminosalicylic acid (PAS) in human plasma. The technique consisted of a protein precipitation extraction, followed by high performance liquid chromatography with tandem mass spectrometry (LC-MS/MS) detection. Rilmenidine was used as the internal standard (ISTD). Analyte mean extraction yields determined were ~100.3% (CV % = 3.3). The extraction procedure was followed by liquid chromatographic separation using a Phenomenex Synergi Hydro-RP (150 x 2.0 mm, 4µm) analytical column. An isocratic mobile phase containing methanol, water and formic acid (40:59.8:0.2, v/v/v) was used at a flow-rate of 300 µl per minute. The retention times for PAS and rilmenidine were, ~2.4 and ~1.6 minutes, respectively. An AB Sciex API 3000 mass spectrometer at unit resolution in the multiple reaction monitoring (MRM) mode was used to monitor the transition of the protonated precursor ions m/z 154.1 and m/z 181.2 to the product ions m/z 80.2 and m/z 95.2 for PAS and the ISTD, respectively. Electro Spray Ionisation (ESI) was used for ion production. Accuracy and precision were assessed over three consecutive, independent runs. The calibration curve fits a quadratic (weighted by 1/x concentration) regression for PAS over the range 0.391 – 100 µg/ml, based on peak area ratios. A 1:1 and 1:4 dilution of the QC Dilution sample showed that concentrations of up to 160 µg/ml of PAS in plasma could be analysed reliably when diluted into the calibration range. Endogenous matrix components were found to have an insignificant effect on the reproducibility of the method, when human plasma originating from eight different sources were analysed. PAS was found to be stable in human plasma for 21 months kept at ~-80°C, for up to 21 hours at room temperature and when subjected to 3 freeze-thaw cycles. Stock solutions of PAS in methanol were stable for 2 days when stored at ~80°C and for 24 hours when stored at room temperature, ~4°C and ~-20°C. Plasma extracts of the analyte/ISTD ratio were shown to be stable on instrument over a period of ~55 hours. Reinjection reproducibility experiments indicated that an assay batch may be re-injected within 58 hours. Quantification of PAS in plasma was not significantly affected by the presence of haemolysed blood (2%) in plasma and when Lithium Heparin was used as anti-coagulant instead of K3EDTA. The best marker for terizidone pharmacokinetics is the analysis of cycloserine, a small polar drug with limited potential for absorbing UV that makes it difficult to analyse. A method was validated for the quantification of cycloserine in human plasma, and consisted of a protein precipitation extraction and derivatization, followed by high performance liquid chromatography with MS/MS detection. No ISTD was used as no suitable match could be found. The mean extraction yield determined was ~77% (CV% = 10.7). The extraction procedure was followed by liquid chromatographic separation using a Gemini NX C18 (50 x 2.0 mm, 5µ) analytical column. An isocratic mobile phase containing acetonitrile, water and formic acid (30:69.9:0.1, v/v/v) was used at a flow-rate of 300 µl per minute. The retention time for cycloserine was ~ 1.5 minutes. An AB Sciex API 3000 mass spectrometer at unit resolution in the MRM mode was used to monitor the transition of the protonated precursor ion m/z 335.9 to the product ion m/z 157.2 for cycloserine. ESI was used for ion production. Accuracy and precision were assessed over three consecutive, independent runs. The calibration curve fits a quadratic (weighted by 1/x concentration) regression for cycloserine over the range 0.313 – 40.0 µg/ml, based on peak areas. A 1:4 dilution of the QC Dilution sample showed that concentrations of up to 64.0 µg/ml of cycloserine in plasma could be analysed reliably when diluted into the calibration range and no carry over peaks were observed. Endogenous matrix components were found to have no effect on the reproducibility of the method when human plasma originating from six different sources was analysed. Cycloserine was found to be stable in human plasma for up to 18 hours at room temperature, and when subjected to 3 freeze-thaw cycles. Stock solutions of cycloserine in water and methanol were stable for 10 days when stored at ~ -80°C and for 18 hours when stored at room temperature, ~ 4°C and ~ -20°C. Long term stability in plasma has been proven for 17 months at -80°C. Plasma extracts of the analyte were shown to be stable on instrument over a period of ~ 29 hours. Reinjection reproducibility experiments indicate that an assay batch may be re-injected within 29 hours. Cycloserine is stable in whole blood (on ice) for up to 30 minutes. Both validated methods presented performed well on clinical samples generated from a multi drug resistant TB (MDR-TB) research study in children dosed with PAS and terizidone.